IMPACT OF COVID-19 IN EDUCATION DOMAIN: AN ANALYSIS IN TWIN CITY OF ODISHA, INDIA - Baral, Sukanta Kumar (International Journal of Research -GRANTHAALAYAH, 2020)
The COVID era is responsible for generating repercussions across the globe. These are responsible for generating tectonic shift in several domains. The educational sector is one of them. With forced lockdowns, stay at home and be safe being the norm, educational sector is witnessing the advent of online medium of instructions of teaching. This paper is an attempt to seek answer to the question. An extant review of literature resulted in the following research questions (a) In the context of education what is means to be sustainable? and (b) What means and mechanisms are needed to remain sustainable? The sample techniques are purposive and the sample size is 314 though the authors have targeted the sample size of 500. The data analysis was done by applying descriptive statistics and exploratory data analysis. The research implications of the study is the realisation of the fact that COVID is here to stay and that new variables are identified which form the new areas of research. The future recommendation arising out of the study is the fact findings can be customized to suit the applicability to the specific educational institution. A large sample size would have provided more insight into the behaviour of the variables and their interactions. The conclusion of the study stems from the fact COVID has generated the need for focussing the sustainability. The sustainability inn itself is different for different components of educational eco-system and that different means and mechanisms are adopted to ensure that sustainability is maintained.